2021
DOI: 10.1371/journal.pone.0253509
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and peripheral psychophysiological correlates in the management of induced pain: A systematic review

Abstract: Cognitive reappraisal and acceptance strategies have been shown to be effective in reducing pain experience and increasing pain tolerance. However, no systematic reviews have focused on the relationship between the use of these two strategies and peripheral physiological correlates when pain is experimentally induced. This systematic review aims to summarize the existing literature that explores the relationship between emotion regulation strategies (i.e., cognitive reappraisal and acceptance) and peripheral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…They acknowledged that negative emotions such as stress and thoughts reduce pain tolerance and vice versa. Consistent with many previous studies,[ 30 31 32 33 ] the present findings showed that awareness of the impact of emotions and emotional control plays a vital role in pain resilience. In line with the current study’s findings, West et al .…”
Section: Discussionsupporting
confidence: 93%
“…They acknowledged that negative emotions such as stress and thoughts reduce pain tolerance and vice versa. Consistent with many previous studies,[ 30 31 32 33 ] the present findings showed that awareness of the impact of emotions and emotional control plays a vital role in pain resilience. In line with the current study’s findings, West et al .…”
Section: Discussionsupporting
confidence: 93%
“…However, heart rate differences were found for induction, but not for anticipation periods. In this sense, the inconsistences found in previous studies suggest that emotion regulation success depend not only on the emotion regulation strategy that is used, but also on the moment when reappraisal is implemented (Jaén et al, 2021a).…”
Section: Introductionmentioning
confidence: 88%
“…In addition, the high heterogeneity in the reappraisal instructions used in laboratory settings, as well as the lack of consistency in the operationalization of the emotion regulation strategies makes it difficult to draw general conclusions on each strategy (Jaén et al, 2021a). Consequently, there is the urgent need to deepen our understanding of the mechanisms underlying clinical interventions to manage negative emotions, and to examine the commonalities and differences of each of these specific processes (Jaén et al 2021a;Arch & Crascke, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation